2013
DOI: 10.1038/npp.2013.289
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Brain Activity During a Reward and Loss Task in Opiate-Dependent Patients Receiving Methadone Maintenance Therapy

Abstract: A core feature of human drug dependency is persistence in seeking and using drugs at the expense of other life goals. It has been hypothesized that addiction is associated with overvaluation of drug-related rewards and undervaluation of natural, nondrug-related rewards. Humans additionally tend to persist in using drugs despite adverse consequences. This suggests that the processing of both rewarding and aversive information may be abnormal in addictions. We used fMRI to examine neural responses to reward and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 41 publications
8
52
0
Order By: Relevance
“…The current result concurs with previous research findings of altered striatal activity for non-drug rewards in substance dependence (Buhler et al, 2010;Bustamante et al, 2014;Diekhof et al, 2008;Gradin et al, 2014;Peters et al, 2011;Wrase et al, 2007) and may be consistent with a sustained striatal reward deficiency syndrome (Blum et al, 2000;Koob et al, 2004) in long-term substance abstinence. There are also high levels of MORs in the caudate (Arvidsson et al, 1995), making this region a credible target for modulation with naltrexone.…”
Section: Independent Bold Activation Reductions In the Alcoholminus Asupporting
confidence: 92%
“…The current result concurs with previous research findings of altered striatal activity for non-drug rewards in substance dependence (Buhler et al, 2010;Bustamante et al, 2014;Diekhof et al, 2008;Gradin et al, 2014;Peters et al, 2011;Wrase et al, 2007) and may be consistent with a sustained striatal reward deficiency syndrome (Blum et al, 2000;Koob et al, 2004) in long-term substance abstinence. There are also high levels of MORs in the caudate (Arvidsson et al, 1995), making this region a credible target for modulation with naltrexone.…”
Section: Independent Bold Activation Reductions In the Alcoholminus Asupporting
confidence: 92%
“…However, decreased reward-seeking behavior is insufficient to explain avoidance differences on the current task, since female controls obtained less reward (fewer points) than male controls but showed no differences on avoidance responding. It is possible that male patients had abnormal learning of both the appetitive and aversive components of the current task 53 or had lower learning rates, which impaired the ability of reinforcement to alter their behavior. 54 …”
Section: Discussionmentioning
confidence: 99%
“…Previous research has reported altered striatal activity for non-drug rewards in substance dependence (Buhler et al, 2010;Bustamante et al, 2014;Diekhof et al, 2008;Gradin et al, 2014;Peters et al, 2011;Wrase et al, 2007) with some evidence for a sustained striatal reward deficiency syndrome (Blum et al, 2000) in long-term substance abstinence. The current finding of increased ventral putamen and caudate activation in ex-smokers suggests that they have an increased motivational signal in a reward-motor network where preparatory responses might be optimized to avoid loss.…”
Section: Greater Striatal Activation In Ex-smokers During Loss Anticimentioning
confidence: 98%